UTILIZING THE IMPLEMENTATION OF TAX LAWS FOR THE WELFARE OF THE PEOPLE BASED ON THE PRINCIPLE OF EQUALITY - Putri Maha Dewi (PT Akselerasi Karya Mandiri, 2023)
Tax Law is one instrument economy a country become more stand out since cross trading enter globalization economy. To carry out government in every country is needed various kinds of support funds because without adequate financial support for the program of activities government No can optimally realize. Required funds in management government No little, so need Lots sources receipt of funds, moreover, accompanied with activity development. Fees Alone is Name set that includes taxes, levies, donations, monopolies, and levies other. Several reception governments such, if simplified can distinguished on reception tax and non- tax revenue. Fees tax to match the principle of equality and achieve a sense of balance as well as justice society, then need something effort legal coercion as such stated in Article 23 paragraph (2) of the 1945 Constitution which has amended in Article 23A amendment to III of the 1945 Constitution. The importance of payment taxes, benefits from payment taxes, and sanctions to be imposed If must tax No obey not enough promulgated by the government to public as must tax. because That is regulation and sanctions related avoidance tax need more emphasized so that give effect wary for dodger’s tax.